2017
DOI: 10.1021/acs.joc.7b01398
|View full text |Cite
|
Sign up to set email alerts
|

Toward Orthogonal Preparation of Sequence-Defined Monodisperse Heteromultivalent Glycomacromolecules on Solid Support Using Staudinger Ligation and Copper-Catalyzed Click Reactions

Abstract: The investigation of heteromultivalent interactions of complex glycoligands and proteins is critical for understanding important biological processes and developing carbohydrate-based pharmaceutics. Synthetic glycomimetics, derived by mimicking complex glycoligands on a variety of scaffolds, have become important tools for studying the role of carbohydrates in chemistry and biology. In this paper, we report on a new synthetic strategy for the preparation of monodisperse, sequence-defined glycooligomers or so-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Here, an advanced method providing the required building blocks was developed streamlining the previous approach to a straightforward 3-step route with greatly improved atom economy and higher yields. 29,[31][32][33][34] In the rst step, one of the two primary amines of diethylenetriamine was protected using trityl chloride. Aerward, the second primary amine was selectively converted using Fmoc-OSu in THF at À78 C, with subsequent addition of an activated acid which carries the desired side chain functionality.…”
Section: Synthesis Of Sequence Dened Oligomersmentioning
confidence: 99%
“…Here, an advanced method providing the required building blocks was developed streamlining the previous approach to a straightforward 3-step route with greatly improved atom economy and higher yields. 29,[31][32][33][34] In the rst step, one of the two primary amines of diethylenetriamine was protected using trityl chloride. Aerward, the second primary amine was selectively converted using Fmoc-OSu in THF at À78 C, with subsequent addition of an activated acid which carries the desired side chain functionality.…”
Section: Synthesis Of Sequence Dened Oligomersmentioning
confidence: 99%
“…[7,10] Through combination of different conjugation methods, we can also obtain heteromultivalent glycomacromolecules presenting diverse carbohydrate ligands at specific positionsw ithin the sequence. [11] Here,w en ow extendt he concept of the so-called precision glycomacromolecules from lineart ob ranched structures. In nature, branched structures are found for variousc arbohydratesa nd carbohydrate-conjugates, for example, polysaccharides as well as glycoproteins.…”
Section: Introductionmentioning
confidence: 98%
“…with the introduction of the fluorenylmethoxycarbonyl (Fmoc) protective group, in combination with a library of tailor‐made building blocks, we can synthesize scaffolds presenting a defined number of functional groups at defined positions along the main chain allowing for conjugation of carbohydrate ligands . Through combination of different conjugation methods, we can also obtain heteromultivalent glycomacromolecules presenting diverse carbohydrate ligands at specific positions within the sequence . Here, we now extend the concept of the so‐called precision glycomacromolecules from linear to branched structures.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, extremely efficient reactions are required to ensure monodisperse formation of peptide chains in high yields. 18,19 Complementary to the synthesis of peptides, Zuckermann et al reported the synthesis of peptoids via solid-phase submonomer synthesis. Polypeptoids are accepted as peptidomimetic polymers [20][21][22] with a substituent on the amide nitrogen, which significantly influences the formation of higher order structures due to suppression of a hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%